Effect of surgical mandibular advancement on pharyngeal airway dimensions: a three-dimensional computed tomography study. Issue 5 (May 2016) - Kochar, G.D.; Chakranarayan, A.; Kohli, S.; Kohli, V.S.; Khanna, V.; Jayan, B.; Chopra, S.S.; Verma, M.
Abstract: The aim of this study was to quantify the changes in pharyngeal airway space (PAS) in patients with a skeletal class II malocclusion managed by bilateral sagittal split ramus osteotomy for mandibular advancement, using three-dimensional (3D) registration. The sample comprised 16 patients (mean age 21.69 ± 2.80 years). Preoperative (T0) and postoperative (T1) computed tomography scans were recorded. Linear, cross-sectional area (CSA), and volumetric parameters of the velopharynx, oropharynx, and hypopharynx were evaluated. Parameters were compared with paired samples t -tests. Highly significant changes in dimension were measured in both sagittal and transverse planes ( P < 0.001). CSA measurements increased significantly between T0 and T1 ( P < 0.001). A significant increase in PAS volume was found at T1 compared with T0 ( P < 0.001). The changes in PAS were quantified using 3D reconstruction. Along the sagittal and transverse planes, the greatest increase was seen in the oropharynx (12.16% and 11.50%, respectively), followed by hypopharynx (11.00% and 9.07%) and velopharynx (8.97% and 6.73%). CSA increased by 41.69%, 34.56%, and 28.81% in the oropharynx, hypopharynx, and velopharynx, respectively. The volumetric increase was greatest in the oropharynx (49.79%) and least in the velopharynx (38.92%). These established quantifications may act as a useful guide for clinicians in the field of dental sleep medicine.